Sidelobe suppression in 76-GHz post-wall waveguide-fed parallel-plate slot arrays. - Hirokawa, J. (IEEE Transactions on antennas and propagation)
Sidelobe suppression is demonstrated for 76-GHz post-wall waveguide fed parallel-plate slot arrays for car radar applications. Taylor distribution illumination control is successfully confirmed experimentally in the slot array on the parallel-plate waveguide. The amplitude distribution in the transverse direction is controlled by shaping a quasi-TEM mode and that in the longitudinal direction is realized by the slot coupling control, both in an oversized waveguide. Measured sidelobes are below -22 dB for one-dimensional (1-D) Taylor tapering while those for two-dimensional (2-D) Taylor distribution are below -18 dB. The gain reduction in comparison with that for uniform illumination is less than 1 dB both in the experiment. All these verify the potential of aperture illumination control of the parallel-plate slot arrays